2014
DOI: 10.1007/s00213-013-3427-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene promoter polymorphism (5-HTTLPR) and alcohol use in general population: interaction effect with birth cohort

Abstract: Expression of genetic vulnerability to alcohol use is influenced by birth cohort effects. The 5-HTTLPR genotype is associated with alcohol consumption in general population, but the effect depends on gender and birth cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Studies on the association of the 5-HTTLPR genotype with alcohol consumption have been equivocal in their conclusions, but analysis of the two birth cohorts of the ECPBHS has suggested a possible reason for the inconsistency in findings: Carriers of the s-allele, with higher amygdalar response to threats, have a highly variable association with alcohol use. Specifically, we found a statistically highly significant genotype × gender × birth cohort interaction effect on the age of first consumption of half a unit of alcohol [21]: While in the older cohort of the ECPBHS the female s/s homozygotes were the group that started to drink alcohol later than any other group, the female 5-HT-TLPR homozygotes of the younger cohort made the alcohol debut earlier than males and on average at almost three years younger age than their counterparts in the older cohort.…”
mentioning
confidence: 78%
“…Studies on the association of the 5-HTTLPR genotype with alcohol consumption have been equivocal in their conclusions, but analysis of the two birth cohorts of the ECPBHS has suggested a possible reason for the inconsistency in findings: Carriers of the s-allele, with higher amygdalar response to threats, have a highly variable association with alcohol use. Specifically, we found a statistically highly significant genotype × gender × birth cohort interaction effect on the age of first consumption of half a unit of alcohol [21]: While in the older cohort of the ECPBHS the female s/s homozygotes were the group that started to drink alcohol later than any other group, the female 5-HT-TLPR homozygotes of the younger cohort made the alcohol debut earlier than males and on average at almost three years younger age than their counterparts in the older cohort.…”
mentioning
confidence: 78%
“…It is of notice that genotype associations with behavioural measures in these two birth cohorts have not been similar in a variety of previous analyses. Indeed, for behaviours with strong secular changes such as age of alcohol use debut, striking genotype by birth cohort interactions have been revealed (Vaht et al, 2014(Vaht et al, , 2016. These may be related to changes in attitudes toward alcohol use in adolescents and alcohol availability during the societal changes that were very rapid in some of the countries of Central and Eastern Europe during the period when the two birth cohorts were in critical age .…”
Section: Discussionmentioning
confidence: 99%
“…One study in a Han Chinese population reported that alcohol-dependent patients were more likely to carry the low-functional genotypes of 5-HTTLPR, such as SS, SL G , or L G L G [47], while other studies which considered triallelic functional 5-HTTLPR found no such association between the selected SNP and alcohol dependence [48]. Evidence from animal and human studies supports a role for 5 - HTTLPR gene-environment interactions in the development of excessive alcohol intake [49,50]. Studies in humans have provided evidence for earlier and heavier alcohol use only among 5 - HTTLPR S allele carriers following stressful life events [51,52], while another recently published study found no significant environment  ×  genotype interaction among males, but it found that in the general population male carriers of 5-HTTLPR SS reported the highest consumption of alcohol [50].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from animal and human studies supports a role for 5 - HTTLPR gene-environment interactions in the development of excessive alcohol intake [49,50]. Studies in humans have provided evidence for earlier and heavier alcohol use only among 5 - HTTLPR S allele carriers following stressful life events [51,52], while another recently published study found no significant environment  ×  genotype interaction among males, but it found that in the general population male carriers of 5-HTTLPR SS reported the highest consumption of alcohol [50]. In risk settings, binge drinking decreased with each copy of the S allele [53].…”
Section: Discussionmentioning
confidence: 99%